Filosofía, Universidad y Sociedad - Pardo, José Luis (Logos. Anales del Seminario de Metafísica, 2003)
The Doxa commonly accepted by the society and the university states that philosophy practiced in Univestity Departments is a socially useless activity. This belief tranquilizes the society and provides to the professionals of philosophy the distinction marks of which they extract his symbolic prestige, but hides an inadvertent reality: the multiple extra-academic informal connections that take place between philosophy and society, and that have fed the birth of hybrid literary-intellectual territories with a strong practical implantation. The reforms that are to undergo in the next years the Spanish educative space demand with increasing insistence the adaptation of university Departments to the necessities of the society and, therefore, the taking in consideration of that inadvertent connection. If, by virtue of the old corporative prejudices, the professional philosophy does not accept the work of critical control of that informal periphery, is possible that it cannot reflectively direct his process of transformation in agreement with the requirements of a democratic society.